Crossing cultural borders: results of an intervention on community college biology students' understanding and acceptance of evolution. Issue 4 (4th March 2021) - Green, Kathryn; Delgado, Cesar
ABSTRACT: Evolution is an essential underlying concept in biology. Previous research demonstrates that many obstacles exist that prevent successful teaching and learning about evolution. This research study used the theoretical framework of cultural border crossing and its underlying cognitive explanation, collateral learning, to design an intervention for community college students in an introductory biology class for non-science majors. Cultural border crossing explains that learners might encounter extensive differences between their home cultures and the culture of the science classroom and may need assistance in navigating the crossing of these cultural borders. Collateral learning is the cognitive mechanism that can be used to resolve potentially conflicting schemata within one's cognitive structure. Quantitative data show a small positive effect on the students' understanding and acceptance. Qualitative data show how students' understanding and acceptance of evolution change after the intervention and when cultural border crossing and collateral learning occur. Results and themes suggest that more research is needed on how students' cultures influence their learning about evolution and how educators can best facilitate learning among students with various cultural beliefs about the diversity of life on Earth.